Are native bees in Brazil at risk from the exposure to the neonicotinoid imidacloprid? - Conceição de Assis, Josimere; Tadei, Rafaela [UNESP]; Menezes-Oliveira, Vanessa B.; Silva-Zacarin, Elaine C.M. (Elsevier, 2022)
All across the world, different countries use Ecological risk assessments (ERA) of pesticides to pollinators as a regulatory tool to understand the safety of pesticide use in agriculture. However, pesticide application is still recognized as one of the main stress factors causing a decline in the global population of bees. In all ERA procedures, the effects of pesticides on the honey bee species Apis mellifera are used as a reference for the effects on all different bee species. To evaluate if tropical native bees are protected by the current risk assessment procedures and to propose improvements to the methods, we assessed the ecological risk of the neonicotinoid imidacloprid posed to native and exotic bee species. The risk was assessed through a low (TIER I) and an intermediate (TIER II) level of analysis. For TIER I the USEPA BeeREX model was used and for TIER II the Species Sensitivity Distribution (SSD) approach was adopted. For the imidacloprid exposure conditions, four different crops were taken into consideration; bean, passion fruit, sunflower and tomato. The imidacloprid risk on native species was assessed both by extrapolating the effects obtained to Apis species, and by using ecotoxicological data from tests performed with native species. In TIER I, the risks calculated through empirical data showed that more than 50% of the non-Apis species presented risk levels of 28–180% higher than those obtained with the extrapolation factor used in the Brazilian pesticide regulation. In TIER II, the SSDs showed that most of the native bees are more sensitive to imidacloprid than the Africanized A. mellifera. This is the first study in which an ERA of a pesticide was conducted on tropical bee species. Here we also present some gaps and perspectives for future studies aiming to improve the risk assessment of pesticides in terrestrial environments.
Keywords: Brazilian bees; Native species; Neonicotinoid; Pollinators; Risk quotient; SSD curve